2012
DOI: 10.1186/1471-2350-13-112
|View full text |Cite
|
Sign up to set email alerts
|

PXR and CAR single nucleotide polymorphisms influence plasma efavirenz levels in South African HIV/AIDS patients

Abstract: BackgroundThis study investigated variation in NR1I2 and NR1I3 and its effect on plasma efavirenz levels in HIV/AIDS patients. Variability in plasma drug levels has largely led research on identifying causative variants in drug metabolising enzyme (DME) genes, with little focus on the nuclear receptor genes NR1I2 and NR1I3, coding for PXR and CAR, respectively, that are involved in regulating DMEs.Methods464 Bantu-speaking South Africans comprising of HIV/AIDS patients on efavirenz-based treatment (n=301) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 30 publications
2
38
0
Order By: Relevance
“…Lower efavirenz concentrations have been associated with NR1I3 540C>T and NR1I3 1089T>C carriers (TT, CC, respectively) . Relationships between NRII3 540C>T or 1089T>C and CL/F was not confirmed in ENCORE1 patients.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Lower efavirenz concentrations have been associated with NR1I3 540C>T and NR1I3 1089T>C carriers (TT, CC, respectively) . Relationships between NRII3 540C>T or 1089T>C and CL/F was not confirmed in ENCORE1 patients.…”
Section: Discussionmentioning
confidence: 95%
“…Samples were quantified and normalized to 20 ng/lL. Genotyping for SNPs previously associated with efavirenz PK (CYP2B6 516 G>T (rs3745274), 8,9,13,15 CYP2B6 983 T>C (rs28399499), 10 CYP2B6 15582C>T (rs4803419), 19 CYP2A6*9B (rs8192726), 8 CYP2A6*17 (rs28399454), 8 CYP3A4*22 (rs35599367), 40 NR1I3 (CAR) 540C>T (rs2307424) 7 and NR1I3 1089T>C (rs3003596) 18 ) was performed using real-time polymerase chain reaction (PCR) allelic discrimination assays (C_7817765_60, C_60732328_20, C_7817764_10, C_29560333_20, C_34816076_20, C_59013445_10, C_25746794_20, and C_16194070_10, respectively; Applied Biosystems, Foster City, CA) as previously described. 17,40 PK modeling Nonlinear mixed effects modeling (NONMEM v. 7.2, ICON Development Solutions, Ellicott City, MD) was applied to the data 41 with initial parameter estimates taken from the literature.…”
Section: Gmr (90% Ci) Amentioning
confidence: 99%
“…A large number of SNPs for PXR (NR1I2)- and CAR (NR1I3)- encoding genes are known, several of which are associated with altered expression and/or function of these receptors [69, 68]. For the NR1I2 SNP 63396C>T, located in a putative transcription factor binding site, the 63396T variant associates with elevated PXR expression, increased CYP3A4 expression and decreased plasma levels of the CYP3A4 substrate atazanavir (an anti-retroviral drug).…”
Section: Genetics Epigenetics and Interindividual Differences In Dmentioning
confidence: 99%
“…When stratifying for the CYP2B6 516G>T genotype, the significant effect is only seen in patients with the CYP2B6 c.516 TT genotype [54]. The same study found no statistically significant association with other NR1I3 or NR1I2 SNPs and EFV plasma concentrations, including rs2307424 [54]. …”
Section: Pharmacogeneticsmentioning
confidence: 99%